Unveiling the increasingly altered patterns of wetland ecosystem functional diversity in the lower Delta of the Paraná River - Aquino, Diego Sebastián (2022)
Since climate, environmental and anthropic controls affect ecosystem functioning simul taneously, wetlands are permanently changing at different spatio–temporal scales. Thus, regionalizations based not only on structural, but also on functional features of ecosys tems constitute a much-needed baseline towards proper decision-making and environ mental management in the context of land degradation and water management infrastructure. Our aim was to identify and characterize the spatio-temporal patterns of ecosystem functional diversity in a highly diverse and altered mosaic of wetland ecosys tems and assess its environmental and anthropic controls. The characterization was based on satellite-derived functional units (FUs), involving seven rasterized traits derived from complementary time-series decomposition techniques applied to a 15-year n…..v…… d… i….. (NDVI) product (2001–2015). The study area exhibited a vast functional heterogeneity, strongly related to differing anthropic and hydro-geomorphological fea tures. Vegetation dynamics were increasingly restricted by the precipitation regime in areas naturally or anthropically decoupled from the flood pulse, which also exhibited the lowest ecosystem functional richness. Depicted as morpho-dynamically stable, areas still subject to recurring overflow events and higher water permanence exhibited sustained NDVI values during the growing season. Our study addresses a proper case of globally widespread land degradation processes occurring across several wetland ecosystems on Earth. Particularly, development of unrestricted water management infrastructure and decouplement from the hydrologic regime suggests an ongoing loss of ecosystem func tional diversity and constrained carbon gain dynamics. In this context, the spatio temporal accuracy of our study constitutes a reliable and replicable foundation, suitable for improvement of environmental management in wetland ecosystems.